The healthy moms and babies app to prevent postpartum depression: analysis of user-profiles and dropout cases - Rodriguez-Muñoz, María F.; Kovacheva, Katina; García-López, Helena S.; Le, Huynh-Nhu; Ruiz, Natalia; Olivares, Maria Eugenia; Izquierdo Mendez, Nuria; Coronado, Pluvio (Frontiers in Public Health, 2023)
Introduction: Perinatal depression affects mothers, babies and society. Preventive interventions are needed, but face barriers to access. E-health interventions could be an effective and accessible option. To date, few studies have attempted to understand the use of mobile health (m-health) applications and why they are not more widely used. This study aims to understand the demographic characteristics of enrolled participants and examine dropout patterns through the Healthy Moms and Babies app.Methods: A longitudinal study was conducted with a sample of 511 women recruited between 2020 and 2022. Data were collected from the app, including sociodemographic information, the participant´s progress through the modules of the app, and the permissions granted to use the app.Results: Out of the 511 women who completed the initial form to initiate participation, 279 downloaded the app and completed the evaluation. Results indicated that granting permission to be notified about the module's availability is related to an increase in the use of the first modules.Conclusions: This study shows the importance of establishing follow-ups in the use of mobile apps during the perinatal period.